Organizational forms for global engagement of firms - Sprios Bogheas; Holger Görg (Kiel Institute for the World Economy (IfW), 2008)
Global engagement of firms can take a variety of forms. We argue that there are considerable advantages of developing models that allow for a wide set of alternatives of organizational form. We illustrate this firstly using plant level data which allows us to distinguish firms that serve only the domestic market, firms that export final goods abroad, firms that outsource abroad the production of some of the intermediate inputs abroad, firms that own foreign plants abroad, and firms that do more than one of those activities. In our estimation we consider the relationship between productivity all the choice of organizational form. We then present a simple model of the firm that is flexible enough to capture the trade-offs between a great variety of organizational forms.
Keywords: F21; F23; 330; Organizational forms; multinationals; Multinationales Unternehmen; Organisationsstruktur; Internationale Markteintrittsstrategie; Produktivität; Unternehmensentwicklung; Schätzung; Irland